Development and Validity of the Coaching Leadership Scale - Cho, Eunhyun; Tak, Jinkook (Korean Journal of Industrial and Organizational Psychology, 2011)
The purpose of this study was to develop the coaching leadership scale and to examine the validity of the scale and the effect of coaching leadership on organizational attitude. 125 preliminary items and 8 factors of the coaching leadership scale were obtained based on contents analyses of relevant articles, focus group interview, executive coach interviews, and open questionnaires. I used an on-line survey to collect data. The initial coaching leadership scale was distributed to 293 employees for the first sample and 200 employees for the second sample. Results of exploratory factor analyses of the scale showed that the four factor solution with 38 items fit the data best. To test the validity of the scale, the questionnaire was distributed to 600 employees who were working in various types of companies. In order to check cross-validity of the scale, the total group was divided into two sub-groups with 300 employees of each group. 4 factors(respect, goal-setting and feedback, changing the view point, and belief of the growth potential of subordinates) with 24 items were obtained based on exploratory factor analyses for the first sub-group. This four-factor solution was supported by an confirmatory factor analysis for the second sub-group. The coaching leadership scale was significantly correlated with various criteria such as self-efficacy and supervisor trust, organizational citizenship, and organizational commitment, confirming criterion related validity of the scale. Finally, the implications and limitations of this study and the directions for the future research were discussed.